Exploration of the mechanism of Lithospermum erythrorhizon oil in treating atopic dermatitis based on network pharmacology and experimental validation of the PI3K-Akt pathway regulation - Weisheng Hu; Yinlan Wang; Yingjie Zhou; Junbao Shi; Zengyan Li; Xiaoling Jiang; Qinyuan Wu; Changming Zhong; Huilan Weng; Sijie Ouyang; Yuan Jing; Xianxiang Cai; et al. (Heliyon)
Objective: This study aimed to explore the molecular mechanisms of Lithospermum erythrorhizon oil in treating atopic dermatitis (AD), with a particular focus on its regulatory effect on the PI3K-Akt signaling pathway. Methods: Utilizing a network pharmacology approach integrated with experimental validation, we identified active components and potential targets of Lithospermum erythrorhizon oil via TCMSP, ChemSrc, PubChem, and PharmMapper. Common targets were selected by intersecting these with AD-related targets from GeneCards. A protein-protein interaction (PPI) network was built using STRING, and functional analysis Gene Ontology (GO) and pathway enrichment Kyoto Encyclopedia of Genes and Genomes (KEGG) were performed on Metascape. A Gene-miRNA regulatory network was constructed on miRTarBase and NetworkAnalyst, with miRNA functions annotated by miEAA. An AD mouse model induced by DNCB was established to evaluate Lithospermum erythrorhizon oil's therapeutic efficacy, its influence on inflammatory markers, and the PI3K-Akt pathway. Results: Fifteen common targets were found to be crucial in AD pathogenesis. The PPI network, constructed using STRING, revealed interactions among 13 nodes and 42 edges, with Cytoscape analysis highlighting 10 core targets. GO and KEGG analyses were significant in biological processes like cell migration and inflammatory response regulation, and in pathways such as IL-17 signaling and PI3K-Akt signaling. The Gene-miRNA network suggested Lithospermum erythrorhizon oil may regulate miRNAs like hsa-mir-124-3p and hsa-let-7b-5p. Experimental results showed that Lithospermum erythrorhizon oil significantly improved AD symptoms in mice, reduced IL-4 and IL-13 levels, and decreased p-PI3K, p-PI3K/PI3K, p-Akt, and p-Akt/Akt expression, inhibiting PI3K-Akt pathway activation. Conclusion: Lithospermum erythrorhizon oil exerts multi-target, multi-pathway therapeutic effects in AD, potentially through suppressing Th2-mediated immune responses and the PI3K-Akt signaling pathway, suggesting novel avenues for AD treatment strategies.